Analysis of turbulent flows with computer programs - Cebeci, Tuncer (Butterworth-Heinemann, 2013)
Analysis of Turbulent Flows is written by one of the most prolific authors in the field of CFD. Professor Tuncer Cebeci calls on both his academic and industrial experience from teaching aerodynamics at SUPAERO, and directing DMAE at ONERA when presenting this work. Each chapter has been specifically constructed to provide a comprehensive overview of turbulent flow and its measurement. Analysis of Turbulent Flows serves as an advanced textbook for PhD candidates working in the field of CFD, making this book essential reading for researchers, practitioners in industry and MSc and MEng students. Key features include; An overview of the development and application of Computational Fluid Dynamics (CFD), with real applications to industry A free-to-access companion website which contains computer programs suitable for solving non-linear equations that arise in modeling turbulent flows Contains a unique section on 'Short-cut' methods - simple approaches to practical engineering problems. About the author; Professor Tuncer Cebeci Chair of the Department of Aerospace Engineering, California State University, Professor Cebeci is widely regarded as an expert in the field of Turbulent Flows and has received many accolades for his work. He was named the first Distinguished Professor in the California State University System, and he received numerous awards including Fellow of the American Institute of Aeronautics and Astronautics. He also received the Presidential Science Award from Turkey. An overview of the development and application of Computational Fluid Dynamics (CFD), with real applications to industry. A free-to-access companion website which contains computer programs suitable for solving non-linear equations that arise in modeling turbulent flows. Contains a unique section on 'Short-cut' methods - simple approaches to practical engineering problems.